Quality traits of fresh and dry-cured loin from Iberian x Duroc crossbred pig in the Montanera system according to slaughtering age. (December 2020) - Ortiz, Alberto; García-Torres, Susana; González, Elena; De Pedro-Sanz, Emiliano Jesús; Gaspar, Paula; Tejerina, David
Abstract: Iberian x Duroc cross grower pigs of similar weight, but 12, 10 and 8 months of age, were finished using the Montanera system to study effects on fresh and dry cured loin quality. Pigs were slaughtered simultaneously at 16, 14 and 12 months of age (IBxD16, IBxD14 and IBxD12) and l ongissimus thoracis et lumborum were removed and processed into dry-cured loin. Fresh and dry cured loins from the oldest animals (IBxD16) had higher tocopherols, C18:2 n-6 and PUFA as well as higher insoluble collagen, which led to greater hardness. Fresh loin from the youngest animals (IBxD12) had the lowest myoglobin content, redness (a*), chroma and hue angle. No differences in proximate composition or instrumental colour were found in dry-cured loins.